HYDROGRAPHIE ACOUSTIC SYSTEMS - MEASUREMENT PRINCIPLES: HYDROGRAPHIE ACOUSTIC SYSTEMS - MEASUREMENT PRINCIPLES - Stoykov, Evgeni (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Hydrography is an applied science that deals with the study of the bottom and shores of the world ocean (all oceans and seas), lakes, rivers and dams, i.e. all natural and artificial water bodies. Hydrographic research is the study of individual areas of the hydrosphere, including the design, implementation of hydrographic works, processing and analysis of the collected data.